2022
DOI: 10.1002/hsr2.787
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis and allergic reactions to COVID‐19 vaccines: A narrative review of characteristics and potential obstacles on achieving herd immunity

Abstract: Background and Aims: Coronavirus disease 2019 (COVID-19) is a highly contagious infection, and new variants of its causative virus continue to emerge all around the world. Meanwhile, mass vaccination represents a highly effective measure to reduce the disease burden. Not only do vaccines immunize individuals, but they also protect the entire population through achieving herd immunity. They are composed of various ingredients, some of which may induce hypersensitivity reactions, namely anaphylaxis and cutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…In this particular instance, the delivery of the COVID-19 vaccine may have worsened the existing allergy to omalizumab, as the coughing worsened after each administration. It is likely that an allergy to omalizumab and the COVID-19 vaccine will amplify each other when it is mediated by an IgE mechanism ( 18 ). To reduce the risk of anaphylaxis caused by an allergy to omalizumab, which can be tested for if an adverse reaction to the COVID-19 vaccination is already known, the presence of an allergy to polysorbate should be evaluated first.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular instance, the delivery of the COVID-19 vaccine may have worsened the existing allergy to omalizumab, as the coughing worsened after each administration. It is likely that an allergy to omalizumab and the COVID-19 vaccine will amplify each other when it is mediated by an IgE mechanism ( 18 ). To reduce the risk of anaphylaxis caused by an allergy to omalizumab, which can be tested for if an adverse reaction to the COVID-19 vaccination is already known, the presence of an allergy to polysorbate should be evaluated first.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated the dose-dependent safety and tolerability of LNP-based nucleic acid vaccines is suitable for a pandemic response, although improved safety profiles would appear to be desirable for non-emergency situations [56]. Allergic reactions have been attributed to polyethylene glycol and polysorbate excipients within these vaccines, and post-licensure safety monitoring has observed increased risk of myoand pericarditis in recipients that have prompted updates to regulatory guidelines for trial conductance [57][58][59][60][61]. As an alternate delivery formulation, the LION TM family of highly stable cationic emulsions was developed.…”
Section: Developmentmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has emerged as a global pandemic since its outbreak in December 2019. , As of January 2023, roughly three years after its initial breakout, COVID-19 continues to pose serious threats to human health and public safety, with more than 762-million confirmed cases and 6.8 million deaths worldwide . Although vaccination continues to remain the most effective therapeutic strategy to protect people against serious illness or death from COVID-19, the emergence and global spread of highly contagious SARS-CoV-2 variants harboring spike mutations have raised concerns about vaccine effectiveness due to the potential of these variants to escape existing SARS-CoV-2 neutralizing antibodies. In addition, individuals with immunocompromised conditions often exhibit significantly low seroconversion rates after vaccination, resulting in poor vaccine protection against COVID-19. , The current vaccination approach is also limited in its ability to protect people with historically severe allergic reactions to vaccines by putting this population at an increased risk of life-threatening hypersensitivity adverse events such as anaphylaxis after getting vaccinated, thereby giving rise to hesitation in receiving COVID-19 vaccines and bringing challenges to achieving herd immunity against this infection. , Thus, despite the wide availability of vaccines, there is still an urgent need for the development of other broadly protective interventions to halt the devastation of the evolving pandemic. Among therapeutic interventions, drug discovery efforts in developing specific antiviral agents against SARS-CoV-2 proffer a powerful addition to the host defense mechanisms for combating COVID-19 and eradicating future pandemics.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 The current vaccination approach is also limited in its ability to protect people with historically severe allergic reactions to vaccines by putting this population at an increased risk of life-threatening hypersensitivity adverse events such as anaphylaxis after getting vaccinated, thereby giving rise to hesitation in receiving COVID-19 vaccines and bringing challenges to achieving herd immunity against this infection. 9 , 10 Thus, despite the wide availability of vaccines, there is still an urgent need for the development of other broadly protective interventions to halt the devastation of the evolving pandemic. Among therapeutic interventions, drug discovery efforts in developing specific antiviral agents against SARS-CoV-2 proffer a powerful addition to the host defense mechanisms for combating COVID-19 and eradicating future pandemics.…”
Section: Introductionmentioning
confidence: 99%